Cerebellar culmen-substantia nigra tract assisted rehabilitation post stroke: a case report - 石田哲朗; Tomonori, Murayama (Brazilian Journal of Case Reports, 2022)
An 88-year-old right-handed man was admitted to our hospital for cognitive impairment and right-sided paralysis. His head non-contrast computed tomography (CT) showed large low-density areas (LDA) and fibrous structures in the left occipital and temporal lobe regions. Despite the fact that it had been more than 10 years since his stroke, rehabilitation was effective. This is a rare case in which cerebellar culmen -substantia nigra tract assisted rehabilitation after stroke.